Inside the 'black box': process evaluation of the upbeat pilot trial. (7th June 2011) - Sandall, J; Hunt, C; Poston, L; Briley, A; Oteng-Ntim, E; Khazaezadeh, N; Robson, S; Bell, R
Abstract : The UK Better Eating and Activity Trial (UPBEAT) aims to improve pregnancy outcome in obese women by improving blood sugar control through a dietary and activity intervention delivered in eight group sessions by a health trainer. The MRC framework for trials of complex interventions states that findings should be informed by a process evaluation specifying how the intervention works, for whom and in what circumstances. This nested process evaluation aimed to provide greater understanding of the socio-cultural context within which the trial is delivered, and the acceptability, feasibility and fidelity of the intervention. The pilot trial ran from February 2010 until January 2011 in four sites in England. Health trainers' audio diary of each session, and 40 semi-structured interviews were conducted with women in both arms of the trial purposively sampled to ensure a wide variation of ages, ethnicity, parity and body mass index at booking. All data has been transcribed and analysed thematically in NVivo. Few women attended all eight sessions. Barriers included work commitments and childcare issues. Some women felt uncomfortable in the group setting, citing lack of common ground with others, unable to identify with larger women and disliking others in the group. While some women felt that they gained support from the group sessions, others did not feel that they learnt anything, and could have got the information from the handbook, which all women found helpful. Amendments to the intervention to include one to one and telephone sessions are currently being made to inform the main trial.